Fostering engagement using a wearable for self-tracking assisted psychotherapy with refugees diagnosed with complex PTSD: a feasibility pilot study - Riisager, Lisa G.; Huniche, Lotte; Larsen, Jakob Eg; Christiansen, Thomas Blomseth; Kring, Lotte; Palic, Sabina; Moeller, Stine Bjerrum (Frontiers in Psychiatry, 2025)
BackgroundTo address the unique challenges faced by refugees diagnosed with complex post-traumatic stress disorder (CPTSD), psychotherapy needs to be personalized. The integration of self-tracking instruments into therapy offers a promising approach to personalizing treatment. This feasibility pilot study develops and explores a preliminary self-tracking assisted treatment concept using a wearable self-tracking instrument called the One Button Tracker (OBT). The OBT is a single-purpose self-tracking instrument, designed to track subjectively experienced phenomena.MethodsThe feasibility pilot study adopted a participatory action research design, involving close collaboration between two therapists, two refugees diagnosed with CPTSD, and a research team. Quantitative data was collected from the OBT and qualitative data consisted of semi-structured post-treatment interviews and session logbooks. Reflexive thematic analysis was used for the interpretation of interview data. Quantitative data was used descriptively.ResultsThe integration of OBT into psychotherapy with refugees was found to be feasible, marked by consistent high engagement as seen in the self-tracking data. Five themes were generated from the interview analyses, across two contexts: therapy sessions (navigating between precision and alliance with the OBT, and data usefulness in therapy) and daily life (paradox of awareness, OBT as a sign of treatment, and following the Doctor’s orders).ConclusionThis feasibility pilot study illustrates the feasibility and therapeutic potential for integrating the OBT into psychotherapy for refugees with CPTSD to enhance engagement and personalization. The findings emphasize the necessity of an adaptive, personalized approach, vigilance regarding potential risks, and consideration of cultural factors. Further research is needed to refine this novel therapeutic approach.